2013
DOI: 10.18097/pbmc20135904378
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric state investigation of flavocytochrome CYP102A1 using afm with standard and supersharp probes

Abstract: Atomic force microscopy with two types of probes – standard (radius of curvature R~10 nm) and supersharp (R~2 nm) – was used to determine CYP102A1oligomeric state. CYP102A1 images were obtained in a liquid, air and vacuum environment using the standard probes, also a ratio of monomers to oligomers (a) of CYP102A1 were determined as a=0.48:0.52. At the same time use of standard probes did not allow to resolve the structure of these oligomers. Supersharp probes allowed to obtain the data about the monomers to ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The information on the enzyme’s structure is very important for elucidation of the reaction mechanisms of (I) and (II) groups. AFM was capable of visualizing and obtaining the height of protein molecules and protein-protein complexes forming in those systems [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] in a tapping mode. Analysis of the density distribution with height ρ ( h ) and its approximation allowed for the determination of parameters of single proteins as well as protein complexes.…”
Section: Atomic Force Microscopy (Afm) Visualization Of Proteinsmentioning
confidence: 99%
“…The information on the enzyme’s structure is very important for elucidation of the reaction mechanisms of (I) and (II) groups. AFM was capable of visualizing and obtaining the height of protein molecules and protein-protein complexes forming in those systems [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] in a tapping mode. Analysis of the density distribution with height ρ ( h ) and its approximation allowed for the determination of parameters of single proteins as well as protein complexes.…”
Section: Atomic Force Microscopy (Afm) Visualization Of Proteinsmentioning
confidence: 99%
“…That is why this system is often used as an object in enzymatic reaction studies [10] , [11] , [12] , [13] , [14] and was chosen in the present work to investigate the microwave emission. Besides, in our earlier study on the same it was shown by atomic force microscopy that the functioning of the enzyme is accompanied by fluctuations of the protein globule [12] , [13] , [14] , [15] , [16] . These fluctuations are able to cause disturbances of aqueous environment of the cytochrome CYP102 A1 molecules thereby generating the microwave emission from the whole solution.…”
Section: Introductionmentioning
confidence: 85%
“…Комбинация АСМ-фишинга с МС анализом имеет большие потенциальные возможности для медицинской протеомики. Это связано с тем, что АСМ-фишинг позволяет одновременно вылавливать, концентрировать и визуализировать низкокопийные белки и их комплексы [4][5][6][7][8], а высокочувствительный МС анализ позволяет идентифицировать выловленные белки. С помощью АСМ-фишинга возможна регистрация белков в диапазоне концентраций 10 -14 -10 -16 M [2].…”
Section: Introductionunclassified